Estrogen Replacement Reduces Oxidative Stress in the Rostral Ventrolateral Medulla of Ovariectomized Rats. (10th November 2015) - Hao, Fan; Gu, Ying; Tan, Xing; Deng, Yu; Wu, Zhao-Tang; Xu, Ming-Juan; Wang, Wei-Zhong
Abstract : Cardiovascular disease prevalence rises rapidly after menopause, which is believed to be derived from the loss of estrogen. It is reported that sympathetic tone is increased in postmenopause. The high level of oxidative stress in the rostral ventrolateral medulla (RVLM) contributes to increased sympathetic outflow. The focus of this study was to determine if estrogen replacement reduces oxidative stress in the RVLM and sympathetic outflow in the ovariectomized (OVX) rats. The data of this study showed that OVX rat increased oxidative stress in the RVLM and sympathetic tone; estrogen replacement improved cardiovascular functions but also reduced the level of oxidative stress in the RVLM. These findings suggest that estrogen replacement decreases blood pressure and sympathoexcitation in the OVX rats, which may be associated with suppression in oxidative stress in the RVLM through downregulation of protein expression of NADPHase (NOX4) and upregulation of protein expression of SOD1. The data from this study is beneficial for our understanding of the mechanism of estrogen exerting cardiovascular protective effects on postmenopause.